Determinant of World Oil Price and Fed Funds Rate on Indonesia Inflation - Masadi Masadi (Economics Development Analysis Journal, 2017)
The changing global economic cycle may affect the Indonesia inflation, such as world oil prices and Fed Funds Rate. This research aims at analyzing the direct or indirect effects that cause the changes in the world oil prices and the Fed Funds Rate to the volatility of inflation in Indonesia. The analytical tool used in this research is path analysis. The research results is a significant direct effect of the world oil price variable on the inflation, there is a significant direct effect of the Fed Funds Rate variable on the inflation, and there is a significant direct effect of the Bank Indonesia (BI) variable on the inflation. The variable of the amount of money in circulation has no significant direct effect on the Indonesia inflation, there is a significant direct effect of the variables of the world oil prices and the Fed Funds Rate on the money in circulation, and there is a significant direct effect of the Fed Funds Rate variable on the money in circulation. There is a significant direct effect of the world oil price variable on the BI rate, and there is significant direct effect of the Fed Funds Rate variable on the BI rate.